In Silico Genome-wide Identification and Characterization of ERF1 Transcription Factors in Citrus Sinensis and Citrus clementina for Potential CTV Resistance - Singh, Ngangbam Sana; Tyagi, Wricha; Meetei, Ng Tombisana (International Journal of Bio-resource and Stress Management, 2026)
A study was conducted in silico during October to December, 2025, at College of Post Graduate Studies in Agricultural Sciences, CAU (Imphal), Umiam, Meghalaya (793 103) India, to understand the role of ERF1 genes in conferring resistance to Citrus tristeza virus (CTV) in citrus species, primarily focusing on genome-wide identification of ERF1 genes in Citrus sinensis and Citrus clementina, their domains and gene structure. CTV infection in citrus species cause symptoms like stem pitting and decreased yield, and posed a serious threat to the world’s citrus production. The AP2/ERF superfamily’s ethylene response factor (ERF) transcription factors are essential for plant stress responses, including pathogen resistance through GCC box binding and hormone signaling pathways. ERF1 orthologs in Citrus sinensis and Citrus clementina were yet to be characterized. With this idea, an in-silico genome-wide identification of putative ERF1 orthologs was performed using Arabidopsis thaliana AtERF1 (NP_567530.4) as a query via Phytozome BLAST. The top hits were chosen as putative orthologs based on e-value, % identity, and alignment length. Five orthologs were identified each in C. sinensis and C. clementina. Gene structures suggested 1–3 exons with varying GC content; proteins ranged from 167 to 400 aa (MW 18–44 KDa, pI 5.46–10.03). All orthologs identified contained conserved AP2/ERF domain (IPR001471), with some having zinc fingers. Gene ontology predicted DNA binding, transcription factor activity, nucleus localization, and many roles in biological processes, including chitin response, vascular development, and defensive signaling. These results clarified the structural diversity and functional annotations of ERF1 in citrus, paving the way for future functional studies and crop enhancement techniques that targeted ERF1 genes.